Knee alignment in the transverse plane during weight-bearing activity and its implication for the tibial rotational alignment in total knee arthroplasty. Issue 6 (July 2015) - Yin, Li; Chen, Kaining; Guo, Lin; Cheng, Liangjun; Wang, Fuyou; Yang, Liu
Abstract: Background: The alignment of the knee in the transverse plane is important to the biomechanical functions of the lower limb, and is also associated with the outcomes of the total knee arthroplasty. This study aimed to evaluate the dynamic tibiofemoral alignment in the transverse plane during a weight-bearing activity. Methods: Knee kinematics of weight-bearing flexion from 0° to 120° was obtained in 16 healthy subjects utilizing biplanar radiography and 3D–2D registration techniques. The anteroposterior axes of the femur at multiple flexion angles in the range of knee motion were used to calculate the anteroposterior axis of motion using the least square method. The latter was compared to six surface-derived anatomical axes in the proximal tibia which were most commonly reported in the literature. The relationship between the anteroposterior axis of motion and the tibial tubercle was also quantified. Findings: The anteroposterior axis of motion did not coincide with any of the six anatomical axes tested. Their orientations varied from 10.3° of external rotation to 9.9° of internal rotation in relation to the former. The anteroposterior axis of motion tended to intersect the tibial tubercle between the medial border and the medial 1/3 point. Interpretation: Instead of any of the tested anatomical axes, the transverse knee alignment during functional movements is associated with the medial 1/3 portion of the tibial tubercle. This region may be helpful for the rotational alignment of the tibial components in total knee arthroplasty. Highlights: No single tibial axis can perfectly indicate the dynamic transverse knee alignment. Medial 1/3 of the tibial tubercle relates to the orientation of femur during motion. Medial 1/3 of the tibial tubercle may help the alignment of the tibial components.